The concordance game: A simple tool to estimate breath hold swimming performance and to teach dynamic apnea - Hello, Damien; Vitiello, Damien; Collard, Luc (Frontiers in Psychology, 2022)
Swimming is composed of several phases. One of them is done underwater in apnea. Although this phase takes an important part of the performance, it is not taught much because of the risk it entails. At the same time, learning apnea can reduce the fear of immersion and thus reduce the number of drownings. The pedagogy used in this paper comes from the Game Theory. This paper tested an apnea game based on the agreement between self-prediction and realization of the task. Considering the preliminary level of the 33 sports students involved, the game offered two choices: swimming apnea over 15 or 20 meters (m) with a distribution of payoffs depending on the actual achievement (15m estimated and less than 20m performed = +3 points; 15m estimated and at least 20m realized = +1 points; 20m predicted and less than 20m realized = +2 points; 20m estimated and at least 20m realized = +4 points). Concordance was favored over discordance, including in the swimmer’s comfort zone (15m). Throughout six apneas the results showed that the structure of this game supports the improvement of the estimation of the distances swum. The ‘Concordance Game’ could be offered in Physical Education or in a sports club to learn to swim a longer distance below the surface without forcing.